Study on the shear strength parameters of fibre reinforced soil (palm oil & coconut fibre) / Ahmad Azmi Ahmad - Ahmad, Ahmad Azmi (Faculty of Civil Engineering, 2006)
Geotechnical failures are one of the major problems in design and construction work in Malaysia, generally. This is because general properties of the soil such as strength and bearing capacity can be classified as very loose and weak. For effective and economical, some research in protecting and improving the quality of this type of soil needed. Reinforced Earth Technique is one of the methods to improving the strengths of the soils. It was systematically introduced by a French scientist H. Vidal in 1966. Reinforced Earth is a composite material which is formed by the association of soil and tension resistant reinforcing elements in the form of sheet, strips, nets or mats of metal, synthetic fabrics of fibre-reinforced plastics and arranged in the soil mass in such a way that reinforcement reduces or suppresses the tensile strain which might develop under gravity or boundary forces. Insertion of reinforcing elements in the soil mass modifies the strength of soil, which in shear strength tests appear either as an increased friction angle or cohesion intercept of Mohr envelope. The load deformation response of a reinforced soil can therefore be expected to be an improvement over the unreinforced soil. Keeping in view the above facts, a basic study was carried out in laboratory to study the effect of different percentage of fibres on the shear strength of soil by conducting direct shear tests and triaxial compression test. The effect of various percentages of two different types of fibres was studied by conducted two different test and soil types.